Journal on Data Semantics XV - Spaccapietra, Stefano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The LNCS Journal on Data Semantics is devoted to the presentation of notable work that, in one way or another, addresses research and development on issues related to data semantics. The scope of the journal ranges from theories supporting the formal definition of semantic content to innovative domain-specific applications of semantic knowledge. The journal addresses researchers and advanced practitioners working on the semantic web, interoperability, mobile information services, data warehousing, knowledge representation and reasoning, conceptual database modeling, ontologies, and artificial intelligence. Volume XV results from a rigorous selection among 25 full papers received in response to two calls for contributions issued in 2009 and 2010. In addition, this volume contains a special report on the Ontology Alignment Evaluation Initiative, an event that has been held once a year in the last five years and has attracted considerable attention from the ontology community. This is the last LNCS transactions volume of the Journal on Data Semantics; the next issue will appear as a regular Springer Journal, published quarterly starting from 2012.
Capturing Rhetoric and Argumentation Aspects within Scientific Publications -- A Reference Model for Semantic Peer-to-Peer Networks -- Discovery of Probabilistic Mappings between Taxonomies: Principles and Experiments -- TwigTable: Using Semantics in XML Twig Pattern Query Processing,.Database Semantics Recovery through Analysis of Dynamic SQL -- Ontology Alignment Evaluation Initiative: Six Years of Experience. A Reference Model for Semantic Peer-to-Peer Networks -- Discovery of Probabilistic Mappings between Taxonomies: Principles and Experiments -- TwigTable: Using Semantics in XML Twig Pattern Query Processing,.Database Semantics Recovery through Analysis of Dynamic SQL -- Ontology Alignment Evaluation Initiative: Six Years of Experience.
Keywords: Computer science; Information systems; Database management; Data mining; Information storage and retrieval systems; Artificial intelligence; Computer Science; Data Mining and Knowledge Discovery; Database Management; Information Storage and Retrieval; Information Systems Applications (incl.Internet).; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).